Recycling Model Suggestion for Sustainable Urban Green Areas in Konya - Filiz Çelik (Turkish Journal of Agriculture: Food Science and Technology)
Urban green spaces can be a comprehensive tool to ensure the sustainability of cities. The sustainability of green areas in planning, design, implementation, maintenance and operation processes contributes to the sustainable development of cities as well. There are many ways to ensure that green areas are sustainable from a social, economic and ecological point of view. These include the construction and use of compost under recycling and re-evaluation. The wastes generated as a result of periodic maintenance in urban green areas are disposed together with other wastes in solid waste storage area. However, the use of organic wastes in composting can ensure that green areas are sustainable by reducing both recycling and periodic maintenance costs of green areas. The aim of this study is to improve the idea of recycling and re-evaluation of organic wastes which are emerged in green areas by composting and using them in green areas. For this purpose, a model for composting and replacing fertilizer from organic wastes emerged in green areas of Konya was proposed. Thus, the costs of green areas with very high design, implementation and maintenance expenses will be reduced and they will be sustainable within themselves. The sustainability of urban green spaces will also contribute to Konya's urban sustainability.